New type of progressive provisioning as a characteristic parental behaviour of the crabronid wasp Pemphredon fabricii (Hymenoptera Crabronidae). Issue 2 (4th March 2018) - Bogusch, Petr; Havelka, Jan; Astapenková, Alena; Heneberg, Petr
Abstract : Bees and stinging wasps (Hymenoptera Aculeata) are well known for the great variety of their nesting resources, which include cavities such as empty reed galls. The majority of the species are mass provisioners, and they do not take any care of their brood after provisioning of the nest. Pemphredon fabricii (Crabronidae) nests in abandoned reed galls of Lipara (Diptera Chloropidae) frit flies. However, P. fabricii uses a different type of late progressive provisioning, described here. Nesting females do not make separate chambers for larvae, but instead fill the interior space of the gall with paralysed aphids and lay a single egg at the body surface of one to eight aphids out of the total number of aphids provisioned. Larvae are polyphagous, and are provisioned with at least 21 aphid species. Hyalopterus pruni is the most common prey, since it feeds on common reed in summer. Before pupation, the larvae sort in the cavity from the biggest (turning to females) at the base to the smallest (turning to males) at the apex. In about 20% of nests, the nesting female brings fresh aphids to feed the smallest larvae at the apex of the nest, while the bigger larvae at the bottom reach maturity much earlier. Similar care for larvae at the end of their development has never been reported in any other insect species. Nests of P. fabricii are commonly attacked by two predator beetle and 14 parasitoid species. All these parasites are generalists, and P. fabricii serves as their satellite host.